2010
DOI: 10.12968/bjon.2010.19.sup4.48420
|View full text |Cite
|
Sign up to set email alerts
|

Embedding the quality agenda into tissue viability and wound care

Abstract: The vision for the NHS over the next 5 years is to go from 'good to great', with the government's 5-year plan mapping the journey for the NHS while focusing on improving quality and productivity, using innovation and prevention to drive and connect them. The Department of Health's 2010 report Frontline Care. Report of the Prime Minister's Commission on the Future of Nursing and Midwifery in England identified the need to develop national nursing indicators that measure nurse quality and their impact on patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…With regard to nursing professionals practices in PHC, the studies analyzed reported that nurses play a preponderant role in services administration and management and in care activities coordination carried out by the health staff (41). Thus, nursing professionals perform care and management actions simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to nursing professionals practices in PHC, the studies analyzed reported that nurses play a preponderant role in services administration and management and in care activities coordination carried out by the health staff (41). Thus, nursing professionals perform care and management actions simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the Public Health System of Andalusia (Spain) has developed and set in motion a program promoting the figure of the advanced practice nurse with respect to complex chronic wounds (APN-CCW). The advanced practice nurse undertakes different roles, such as researcher, clinician, change agent, teacher, consultant, and coordinator between levels of healthcare [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Finding ways to prevent the development of skin breakdown and treat it more effectively would be expected to create economic benefits by preventing the need for expensive treatment and equipment. Recognizing and managing pressure ulcers at an early stage to avoid skin lesions turning into pressure ulceration will be absolutely essential (Ousey and White, 2010). The prevention and treatment of pressure ulcers will assist the practioner in meeting the targets set by Comissioning for Quality and Innovations (CQUINS), High Impact Interventions and inspections by the Care Quality Commission.…”
mentioning
confidence: 99%